A safety prompt method for helicopter formation flight - Shanxiao; Huang; Yang; Lu.; Chao; Zhou (My University, 2019)
Aiming at the formation maintenance and comprehensive collision avoidance of the helicopter formation under "Leader-follower" mode, a safety prompt method is proposed. This method is based on the artificial potential field method to maintain formation and prevent collision of terrain and other formation members, which prompts helicopter to perform compound escape maneuver when it encounters obstacles and deviates from formation. After determining the research method, the safety threshold of formation maintenance and comprehensive collision avoidance during helicopter formation flying is discussed. Finally, the correctness of the method is verified by numerical simulation.